Effect of surface condition on strain in semiconductor crystal sample - Serdega, B.K.; Nikitenko, E.V.; Prikhodenko, V.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
Using the optical-polarization technique with polarization modulation, we measured stresses due to surface tension in a single-crystalline silicon sample. Optical anisotropy distribution along the normal to the sample surface was studied at different state conditions, depending on its treatment. It was found that presence of a surface layer in the crystal, with physical properties differing from those in the bulk, gave rise to extended distribution of stresses in the uniform part of the crystal.